Doing Feminist and Activist Learning Outcomes: What Should Students Be Able To Do as a Result of this Women’s and Gender Studies Project/Course/Curriculum? - DeMuth, Danielle M. (Atlantis, 2012)
This essay reviews feminist pedagogical literature on multiple modes of feminist experiential learning, identifies the gap between the women’s studies social justice mission and the courses and assignments developedto achieve it, and proposes the development of activism-specific knowledge and skills goals that are targeted and sequenced across the curriculum.